Women Impoverishment Through the Transfer of Ulayat Land Rights - Wahyuni Retnowulandari (Faculty of Law, Universitas Jenderal Soedirman, 2020)
Indonesia has ratified the Convention on the Elimination of All forms of Discrimination Against Women in 1984. However, the fact remains that women are still often subordinated, including customary land rights such as cases in Lombok, Minangkabau, Riau, and others that prioritize investment that would bring economic benefits adat authorities in which do not involve women. Moreover, the dispute over the ulayat land’s function impacts families’ poverty, including women. Therefore, scientific work with a normative approach using secondary data had sought to compile some of the results of previous empirical research that had raised the case of the transfer of customary land rights. It recommends ways to overcome them by reforming specific regulations regarding the procedure of transferring customary land rights to state rights and equitable ownership rights, and with a gender perspective.Keywords: women’s rights; customary land; gender perspective